2017
DOI: 10.1128/aem.00902-17
|View full text |Cite
|
Sign up to set email alerts
|

A Fatty Acyl Coenzyme A Reductase Promotes Wax Ester Accumulation in Rhodococcus jostii RHA1

Abstract: Many rhodococci are oleaginous and, as such, have considerable potential for the sustainable production of lipid-based commodity chemicals. Herein, we demonstrated that Rhodococcus jostii RHA1, a soil bacterium that catabolizes a wide range of organic compounds, produced wax esters (WEs) up to 0.0002% of its cellular dry weight during exponential growth on glucose. These WEs were fully saturated and contained primarily 31 to 34 carbon atoms. Moreover, they were present at higher levels during exponential growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 47 publications
4
20
0
Order By: Relevance
“…For instance, Alvarez et al [54] demonstrated that R. opacus PD630 accumulated TAG as major inclusions together with some DAG and FFA, which constituted up to 76% and 87% of cellular dry weight when grown on gluconate or olive-oil, respectively, whereas R. rhodochrous accumulated both TAG and WE when cultured in media with glucose as the main carbon source [55]. In the experiments presented in the current study, TAG was identified as a major component of the lipid profiles of some of the sub-Antarctic species tested but there was no evidence of WE synthesis, as shown in other rhodococci species which make detectable but proportionately low quantities of WE [56]. However, TAG was a relatively small proportion of the total lipids detected in the sub-Antarctic strains, possibly because the growth conditions were not optimized for TAG synthesis.…”
Section: Discussionsupporting
confidence: 49%
“…For instance, Alvarez et al [54] demonstrated that R. opacus PD630 accumulated TAG as major inclusions together with some DAG and FFA, which constituted up to 76% and 87% of cellular dry weight when grown on gluconate or olive-oil, respectively, whereas R. rhodochrous accumulated both TAG and WE when cultured in media with glucose as the main carbon source [55]. In the experiments presented in the current study, TAG was identified as a major component of the lipid profiles of some of the sub-Antarctic species tested but there was no evidence of WE synthesis, as shown in other rhodococci species which make detectable but proportionately low quantities of WE [56]. However, TAG was a relatively small proportion of the total lipids detected in the sub-Antarctic strains, possibly because the growth conditions were not optimized for TAG synthesis.…”
Section: Discussionsupporting
confidence: 49%
“…However, alkylphenols may be funneled through ortho- cleavage by oxidizing the para -side chain to 4-hydroxyacetophenone or hydroquinone (Darby et al, 1987). Alternatively, oleaginous Rhodococcus strains such as RHA1 may be modified to use the Aph pathway to produce lipid-based commodity chemicals (e.g., Round et al, 2017) offering a method for valorization of alkylphenols via fatty-acid synthesis in this genus.…”
Section: Discussionmentioning
confidence: 99%
“…Rhodococcus is a genus of mycolic acid-producing Actinobacteria that catabolize a wide variety of aromatic compounds (Yam et al, 2010), including phenols (Kolomytseva et al, 2007; Gröning et al, 2014). These bacteria also have considerable potential as biocatalysts for the industrial production of compounds ranging from nitriles to steroids and high-value lipids (Alvarez et al, 1996; Round et al, 2017; Shields-Menard et al, 2017; Sengupta et al, 2019). In Rhodococcus , phenol catabolism is initiated by a two-component flavin-dependent monooxygenase (PheA1A2; Saa et al, 2010) to generate a catechol.…”
Section: Introductionmentioning
confidence: 99%
“…The organic phase was dried under nitrogen and lipids were suspended in 1 ml chloroform with 1% acetic acid. Aliquots were analyzed by GC-MS as described earlier for FAMEs and free cholesterol (62) and for wax esters (32). Cholesterol and fatty acid methyl-esters (FAMEs) were identified by comparison to authentic standards as well as matching against the NIST database (National Institute of Standards and Technology, v11).…”
Section: Methodsmentioning
confidence: 99%